Physiologial charaterization of the Arctic diatom Thalassisira hyalina under different acclimation temperatures - Linda Rehder (PANGAEA, 2025)
This experiment aimed to understand a the high plasticity of Arctic diatoms towards ocean warming, with a special regard to regulatory mechanisms of photosynthetic and respiratory processes. We therefore assessed the physiological performance of the Arctic diatom Thalassiosira hyalina under sub-optimal (2°C), optimal (6°C) and supra-optimal (10°C) temperatures. The acclimation irradiance was set to 30 μmol photons m-2 s-1 under continuous illumination (24h) and nutrients were repleted. the experiment took place in Winter 2023/2024 in laboratories of the Alfred-Wegener-Institute Bremerhaven. We assessed growth rates, quotas of particulate organic carbon and chlorophyll a, photophyisology using fast repetition rate fluorometry (FRRF) following Schuback et al. 2021, and gas fluxes of O2 and CO2 corresponding to photosynthetic and respiratory processes using membrane-inlet mass-spectrometry (MIMS) following Fock and Sültemeyer 1989 and Rehder et al. 2023. MIMS measurements were done in pH buffered assay medium (pH 7.8) including carbonic anhydrase and equilibrated to ~20% 18O2, to distinguish between photosynthetic O2 production and respiratory O2 consumption in the light. Furthermore, both FRRF and MIMS measurements were performed in photosynthesis-irradiance assays to obtained maximal rates of electron transport, gross O2 production and gross C-fixation. The dataset indicates a metabolic coupling of chloroplasts and mitochondria, which likely reroutes excess reductant from the chloroplasts into mitochondrial respiration.